Muhtawā al-Qirā’ah fi Kitāb Durus al-Lughah al-Arabiyyah li al-Shaff al-Awwal min al-Madrasah al-Tsānawiyyah al-Islāmiyyah li al-Thab’ah 2020 - Muhammad Qadhafi (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
Through this research, the researcher tries to identify the contents of reading skills in Arabic textbook "Durusu al-lughah al-Arabiyah" which apply 2013 curriculum (KMA 183, 2019) for first grade students of Islamic senior high schools, printed in 2020. This study conducted by qualitative research and employed "descriptive analysis technique". The population of this study is Arabic textbook "Durusu al-lughah al-Arabiyah" which apply 2013 curriculum for first grade students of Islamic senior high schools. The procedures of data collection include: 1) Making checklist, 2) Analyzing the Content of textbook, 3) Coding, 4) Tabulating Data, and 5) concluding. The result of the research find that, both listening and reading skills material in the book "Durusu al-lughah al-Arabiyah" which apply 2013 curriculum for first grade students of Islamic senior high schools is a good material according to Abd al-Rahman ibn Ibrahim al-Fauzan in his book "Idla'at li Mu'alimi al-lughah al-Arabiyah li Ghairi Nathiqin Biha”. However, the content reading subject in the textbook "Durusu al-lughah al-Arabiyah" are relevant to the curriculum of 2013 (KMA 183, 2019) in Arabic subject for the first class in the Islamic senior high school.